If it's not what You are looking for type in the equation solver your own equation and let us solve it.
12x-18=6(2x-3)
We move all terms to the left:
12x-18-(6(2x-3))=0
We calculate terms in parentheses: -(6(2x-3)), so:We get rid of parentheses
6(2x-3)
We multiply parentheses
12x-18
Back to the equation:
-(12x-18)
12x-12x+18-18=0
We add all the numbers together, and all the variables
=0
x=0/1
x=0
| 3x^2+21x-5.9=0 | | -0.375c−11=13 | | 4x^2+10x-7=10 | | 1-2*(x*x)=0 | | 5/2x+11=5/2x+11 | | 6n+20=-4n+8(4n-3) | | 2*(x*x)=0 | | 14=n/8 | | M=3/4;b=-12 | | 10^3x-4*10^4=0 | | 2x²=0 | | n-2÷7=2 | | 10+7x=7(-2x+7)+3 | | −3(x−8)=4(−6+14x) | | 15x+4=3x+14 | | 5—t=23 | | 9(e+3)=11e–13 | | 3⁄2c+23=38 | | 8.3a+13=112.6 | | 3/12=x/20 | | -1/2(t+9)+5.75t=3/8 | | -6k-14=-7(2+8k) | | 1-2x²=0 | | x+4/7-x-4/9=4 | | -1/2(t+9)+53/4t=3/8 | | 0=4v+4 | | 30=-5(6n+) | | -4+11x-2=-2x+5x-22 | | 2x^2-13x+9=0 | | 10x-15=5(2x-3) | | -13-x=x+7 | | 4.3=1/x |